PTH-180 Small Bowel Ultrasound and Video Capsule Endoscopy: Complimentary Investigations to Diagnose Small Bowel Crohn'S Disease. (4th June 2013) - McDonnell, M J; Beable, R; Higginson, A; Quine, M A; Pearl, D S
Abstract : Introduction: Crohn's disease affecting the small intestine requires accurate localization, assessment and follow up, to direct and monitor therapy. Video capsule endoscopy (VCE) has an established role in small bowel Crohn's evaluation; however, use is limited by procedure costs and risks of capsule retention. Small bowel ultrasound (SB USS) with doppler is a rapid, inexpensive, dynamic and non-invasive method for assessing activity of Crohn's disease. We present the largest published comparative UK dataset of SB USS and capsule endoscopy in Crohn's disease. Methods: A 5 year retrospective analysis from 2008–2012 was carried out. Patients investigated for suspected small bowel Crohn's disease with SB USS and VCE were included, if one examination occurred within 12 month of the others. VCE findings were graded as mild (apthous ulcers only), moderate (apthous ulcers with mucosal distortion) or severe (apthous ulcers with mucosal distortion and strictures/stenosis). SB USS was graded positive or negative for small bowel Crohn's disease. Both assessments were single operator. Results were expressed as sensitivity, specificity, positive and negative predictive value (PPV and NPV) of SB USS compared with VCE for detection of small bowel Crohn's. Sub-analysis of SB USS findings for VCE-defined severity of small bowel Crohn's disease was carried out. Results: 500 VCE procedures were reviewed, of which 61 fulfilled the inclusion criteria. 19 patients had SB Crohn's on VCE; this was detected in 5 patients by SB USS (sensitivity 26%). 42 patients had no evidence of SB Crohn's on VCE; none of these had SB USS findings (specificity 100%). 56 patients had a negative SB USS, of these 14 VCE studies had findings compatible with Crohn's disease (NPV 75%). All patients with positive findings of Crohn's disease on SB USS had evidence of SB Crohn's on VCE (PPV 100%). Sub-analysis for Crohn's severity was carried out; of 11 VCE patients with moderate to severe Crohn's disease, 5 patients had a positive SB USS (sensitivity 45%), however of 8 patients with mild Crohn's on VCE, no patients had a positive SB USS. Conclusion: SB USS has excellent positive predictive value (100%) and specificity (100%) for detection of SB Crohn's disease. All detected cases were moderate or severe identifying cases at higher risk of capsule retention. Sensitivity of SB USS is 26% rising to 45% in VCE proven moderate or severe disease. It follows that a positive expert SB USS in the context of suspected small bowel Crohn's is a definitive radiological result, on which therapy can be commenced. However, a negative SB USS should be followed by VCE or magnetic resonance enterography (MRE) if clinical suspicion remains. Disclosure of Interest: None Declared.